Soil Chemical Properties and Nutrient Uptake of Cocoa as Affected by Application of Different Organic Matters and Phosphate Fertilizers - Sugiyanto Sugiyanto; John Bako Baon; Ketut Anom Wijaya (Indonesian Coffee and Cocoa Research Institute, 2008)
Effort repair of land quality better be done by simultan namely with application of organic matters and inorganic fertilization. The objective of this research is to study the effect of varied organic matters source and phosphate fertilizers on the chemicals soil characteristic and cocoa nutrient uptake. The experiment was laid experimentally in split-plot design and environmentally in randomized complete block design. The main plot was source of P consisted of, control, SP 36 and rock phosphate in dosage of 200 mg P2O5 per kg of air dry soil. Source of organic matter as sub-plot consisted of control (no organic matter), cow dung, cocoa pod husk compost and sugar cane filter cake, each in dosage of 2.5 and 5.0%. Result of this experiment showed application of cow dung, cocoa pod husk compost and sugar cane filter cake increased content of C, N, Ca exchangeable, Fe available, and pH in soil, and SP 36 increased availability of P in soil. Application of sugar cane filter cake increased N, K, Ca, Mg, and SO4 uptake but did not increase Cl uptake, application of cow dung in dosage 5% increased N, K, and Cl uptake and cocoa pod husk compost dosage 5% increased N and K uptake of cocoa. SP 36 increased Mg uptake of cocoa but rock phosphate did not increase it. They were not interaction between organic matters and phosphate fertilizers to nutrient uptake of cocoa. Nutrient soil content as affected by organic matters correlated with nutrient uptake of cocoa.Key words : soil chemical properties, nutrient uptake, cocoa, organic matter, phosphate fertlizers.